Pengaruh corporate governance, ukuran perusahaan dan leverage terhadap corporate social responsibility (Studi empiris pada perusahaan manufaktur yang terdaftar tahun 2014-2017 di Bursa Efek Indonesia) - Fitriyah, Fitriyah (Indonesia Accounting Journal, 2020)
This study aims to examine the effect of corporate governance, firm size, and leverage on corporate social responsibility on Indonesian listed manufacturing company during period 2014 to 2017. The independent variables of this study are corporate governance, firm size and leverage, while the dependent variable is corporate social responsibility. This study uses panel data to analyze the regression model with assistance of EViews 8. The results of this study indicate that: (1) Board of Commisioners insignificantly effect on corporate social responsibility; (2) the Board of Commissioners independent significant effect on corporate social responsibility; (3) the Audit Committe insignificantly effect on corporate social responsibility; (4) firm size insignificantly effect on corporate social responsibility; and (5) leverage significant effect on corporate social responsibility.